The use of general anaesthesia in special care dentistry: A clinical guideline from the British Society for Disability and Oral Health. (21st January 2022) - Geddis‐Regan, Andrew R.; Gray, Deborah; Buckingham, Sarah; Misra, Upma; Boyle, Carole; ,
Abstract: Background: General anaesthesia (GA) may be required to support the care of those seen in Special Care Dentistry (SCD) services for various reasons, such as enabling extensive dental care for people with severe learning disabilities or severe dental phobia. Guidance is needed for teams delivering SCD using GA due to the potential risks, implications, and costs of using GA to deliver dental care. Aim: To present evidence‐based recommendations, where possible, for teams involved in providing GA for dental care for adults within SCD services. Methods: A multidisciplinary working group, supported by a formal literature search and stakeholder involvement, iteratively produced and refined the recommendations presented. Results: There was little evidence to inform the guidelines. Recommendations are therefore based mainly on the working group's expert consensus opinion. Clinical guidelines are presented as a set of overarching principles followed by six key sections reflecting patients' pathways from referral to dental services through to their care during and after GA. Conclusion: Guidelines are presented to support those providing GA to provide SCD. The need for comprehensive and person‐centered assessment and planning is emphasized.